An enantioselective cascade for simultaneous generation of five quaternary stereocenters from fully substituted enones. Issue 54 (23rd June 2017) - Yang, Shu-Mei; Reddy, Ganapuram Madhusudhan; Wang, Tzu-Ping; Yeh, Yu-Sheng; Wang, Min; Lin, Wenwei
Abstract : A highly stereoselective organocatalytic cascade is developed for efficient synthesis of polycyclic compounds bearing five quaternary stereocenters. Abstract : A highly enantioselective cascade reaction for the generation of five quaternary stereocenters in one-pot operation is reported for the first time in the history of organic synthesis. Cinchona-alkaloid derived hydrogen-bonding catalyst furnished structurally complex cascade products from simple substrates in excellent yields and stereoselectivities.